Simple supercapacitor charging scheme of an electric vehicle on small-scale hardware simulator: a prototype development for education purpose - Adnan Rafi Al Tahtawi; Arief Syaichu Rohman (National Research and Innovation Agency, 2016)
Supercapacitor is one of electrical energy sources that have faster charging-discharging times when compared to other power sources, such as battery and fuel cell. Therefore, it is often used as an additional power source in an electric vehicle. In this paper, a prototype of small-scale electric vehicle simulator (EVS) is built and a simple charging scheme of supercapacitor is used for education purpose. EVS is an electric vehicle prototype which can show the vehicle’s powertrain on small-scale configuration. Main components of this device are two direct current motors (DCMs) with a linked axis of rotation. Therefore one of them will be able to act as a generator. The supercapacitor charging scheme is employed by controlling the relays. The hardware experimental result shows that the averages of charging current are proportional to the maximum slope angle of the road profiles. This scheme is simple due to the EVS utility and it is useful for education purpose.